Advanced Early Years Care and Education : For levels 4 and 5 - MacLeod-Brudenell, Iain. (Oxford : Heinemann, 2004)
This core textbook for foundation degrees covers the content of the 12 core outcomes at the appropriate depth and breadth giving students a complete grounding in the basics of the subject.
Includes bibliographical references and index.
Keywords: Child care -- Great Britain; Early childhood education -- Great Britain; Education